Encyclopedia of flight - Irons-Georges, Tracy (Salem Press, 2002)
" ... The 'Encyclopedia of Flight' bridges the gap between theoretical concepts and practical applications, between scientific information and historical issues ... This ... three-volume work provides information about animal and human-made flight in a way that is accessible to high school and undergraduate students, general readers, and aviation enthusiasts. It examines a wide range of topics, from birds and balloons to jets and spacecraft ..."